Effectiveness of Continuous Endotracheal Cuff Pressure Control for the Prevention of Ventilator-Associated Respiratory Infections: An Open-Label Randomized, Controlled Trial. (22nd August 2021) - Dat, Vu Quoc; Minh Yen, Lam; Thi Loan, Huynh; Dinh Phu, Vu; Thien Binh, Nguyen; Geskus, Ronald B; Khanh Trinh, Dong Huu; Hoang Mai, Nguyen Thi; Hoan Phu, Nguyen; Huong Lan, Nguyen Phu; Phuong Thuy, Tran; Vu Trung, Nguyen; et al.
Abstract: Background: An endotracheal tube cuff pressure between 20 and 30 cmH2 O is recommended to prevent ventilator-associated respiratory infection (VARI). We aimed to evaluate whether continuous cuff pressure control (CPC) was associated with reduced VARI incidence compared with intermittent CPC. Methods: We conducted a multicenter open-label randomized controlled trial in intensive care unit (ICU) patients within 24 hours of intubation in Vietnam. Patients were randomly assigned 1:1 to receive either continuous CPC using an automated electronic device or intermittent CPC using a manually hand-held manometer. The primary endpoint was the occurrence of VARI, evaluated by an independent reviewer blinded to the CPC allocation. Results: We randomized 600 patients; 597 received the intervention or control and were included in the intention to treat analysis. Compared with intermittent CPC, continuous CPC did not reduce the proportion of patients with at least one episode of VARI (74/296 [25%] vs 69/301 [23%]; odds ratio [OR] 1.13; 95% confidence interval [CI] .77–1.67]. There were no significant differences between continuous and intermittent CPC concerning the proportion of microbiologically confirmed VARI (OR 1.40; 95% CI .94–2.10), the proportion of intubated days without antimicrobials (relative proportion [RP] 0.99; 95% CI .87–1.12), rate of ICU discharge (cause-specific hazard ratio [HR] 0.95; 95% CI .78–1.16), cost of ICU stay (difference in transformed mean [DTM] 0.02; 95% CI −.05 to .08], cost of ICU antimicrobials (DTM 0.02; 95% CI −.25 to .28), cost of hospital stay (DTM 0.02; 95% CI −.04 to .08), and ICU mortality risk (OR 0.96; 95% CI .67–1.38). Conclusions: Maintaining CPC through an automated electronic device did not reduce VARI incidence. Clinical Trial Registration: NCT02966392. Abstract : The results of this randomised controlled trial demonstrate that continuous endotracheal cuff pressure control using an electronic automated device does not reduce the occurrence of ventilator-associated respiratory infection (VARI) in intubated patients compared with intermittent control.